The Flexion Withdrawal Reflex Reveals an Increasing Threshold during the First Year of Life and is Influenced by the Infant’s State of Consciousness - Kühne, B.; Stützer, H.; Roth, B.; Welzing, L. (Klinische Pädiatrie, 2012)
The idea that preterm and term infants are capable of experiencing pain is now widely accepted. However, there is still insufficient knowledge how pain perception develops throughout infancy. A promising approach to quantify the level of spinal excitability in infants is to measure cutaneous sensitivity by the flexion withdrawal reflex (WR). In our study we wanted to test how the threshold of the WR develops in healthy infants during the first year of life. Furthermore, we aimed to analyse the impact of the state of consciousness on the reflex threshold.In 44 healthy infants we tested the threshold of the WR with calibrated von-Frey-Filaments at the age of 3 days as well as with 4, 12, 26 and 52 weeks. To analyse the influence of the state of consciousness on the reflex threshold, we documented at 12, 26 and 52 weeks whether the infants were quietly awake or lightly asleep during testing.The median threshold of the WR increased during the first year of life from 1.2 g up to 4.6 g at the age of 1 year. At 12, 26 and 52 weeks we found significantly lower thresholds in sleeping infants compared to infants being awake (p=0.004, p<0.001 and p=0.086, respectively).The threshold of the flexion withdrawal reflex increases during infancy, probably reflecting neuronal maturation processes in the first year of life. Besides postnatal age, the threshold of the WR also depends on the state of consciousness. Therefore, future studies about the WR should consider postnatal age as well as the state of consciousness.
Keywords: infants; pain measurement; flexion withdrawal reflex; von-Frey-Filaments; state of consciousness